Case series of high-risk percutaneous coronary intervention with rotational atherectomy under short-term mechanical circulatory support with TandemHeart in the setting of acute myocardial infarction. Issue 4 (16th September 2020) - Großekettler, Leonie; Schmack, Bastian; Katus, Hugo A; Bekeredjian, Raffi; Raake, Philip
Abstract: Background : TandemHeart is a percutaneous Ventricular Assist Device, most commonly used to provide mechanical circulatory support during high-risk percutaneous coronary intervention and postcardiotomy cardiac failure. However, TandemHeart has not been applied in patients with severe heart failure due to myocardial infarction during high-risk percutaneous coronary intervention with the need for rotational artherectomy (RA) before, so we present a first-in-man case series. Case summary : Three patients with severe HF[Please spell out HF, LA and MI (if necessary).] due to acute myocardial infarction revealed severely calcified lesions of the unprotected left main artery. We successfully used the TandemHeart as percutaneous Ventricular Assist Device during high-risk percutaneous coronary intervention with RA. Discussion : We here report our experience and show that RA under TandemHeart mechanical circulatory support is feasible and safe in case of acute MI.